AGGRESSIVE BEHAVIOR IN ADOLESCENTS AFTER IMPLEMENTING PIK-R AT SMA NEGERI "Z" PEKANBARU IN 2020 (Al Insyirah International Scientific Conference on Health, 2021)
Adolescence is a period of transition from childhood to adulthood. In adolescence, the search for identity is often influenced by negative things, one of which is aggressive behavior. The existence and role of PIK-R within adolescents is very important in helping adolescents obtain information and counseling services. The purpose of this study was to determine the aggressive behavior after PIK-R was implemented in SMA Negeri "Z" Pekanbaru. This research design uses quantitative research. The research instrument used was the Brief Aggression Questionnaire with 12 questions. The sample in this study amounted to 227 high school students. The results showed that after the implementation of PIK-R in SMA Negeri "Z", it was found that the average student / I showed aggressive behavior in the low category, namely 52%. Suggestions from this research, it is hoped that schools will further activate the implementation of PIK-R because the existence of PIK-R is very important for adolescents, especially in directing adolescent behavior towards a better direction.
Keywords: Adolescent; Aggressive Behavior; PIK-R